Complex formation of platelet thrombospondin with histidine-rich glycoprotein. - Leung, L L (1984)
Thrombospondin and histidine-rich glycoprotein are two proteins with diverse biological activities which have been associated with human platelets and other cell systems. Using an enzyme-linked immunosorbent assay, we have demonstrated that purified human platelet thrombospondin formed a complex with purified human plasma histidine-rich glycoprotein. The formation of the thrombospondin-histidine-rich glycoprotein complex was specific, concentration dependent, and saturable. Significant binding was detected when histidine-rich glycoprotein was incubated with thrombospondin immobilized on anti-thrombospondin IgG-coated plates, indicating that the observed complex formation was not due to a thrombospondin interaction with the plastic surface. Sucrose-density-gradient ultracentrifugation of a mixture of thrombospondin and histidine-rich glycoprotein also revealed the formation of fluid-phase complexes, with an estimated stoichiometry of 1 thrombospondin: 3.5 histidine-rich glycoprotein. Fibrinogen, which has been previously shown to bind to absorbed thrombospondin, did not inhibit the formation of the thrombospondin-histidine-rich glycoprotein complex. Histidine-rich glycoprotein complexed with thrombospondin was capable of binding heparin and neutralizing the anticoagulant activity of heparin in plasma. Specific complex formation between thrombospondin and histidine-rich glycoprotein may play a significant role in influencing platelet blood vessel wall interactions as well as modulating the association of various cells with the extracellular matrix.